Poverty, inequality, and human capital development in Latin America, 1950-2025 - Londono, Juan Luis. (Washington, D.C. : World Bank, 1996)
"Presents and analyzes data on extent of and trends in poverty from 1950-94. Uses these trends to project poverty to 2025. Concludes that rapid decreases in poverty will occur only if region devotes significantly more resources to education"--Handbook of Latin American Studies, v. 57.
Includes bibliographical references (p. 37-38).
Zahid
Keywords: Poverty -- Latin America; Income distribution -- Latin America; Human capital -- Latin America